2007
DOI: 10.1103/physrevb.75.115417
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and thermodynamic stability of double-layeredSrTiO3(001)surfaces:Ab initiosimulations

Abstract: Using the B3PW hybrid exchange-correlation functional within density-functional theory and employing Gaussian-type basis sets, we calculated the atomic and electronic structures and thermodynamic stability of three double-layered ͑DL͒ SrTiO 3 ͑001͒ surfaces: ͑i͒ SrO-terminated, ͑ii͒ TiO 2 -terminated, and ͑iii͒ ͑2 ϫ 1͒ reconstruction of TiO 2 -terminated SrTiO 3 ͑001͒ recently suggested by Erdman et al. ͓Nature ͑London͒ 419, 55 ͑2002͔͒. A thermodynamic stability diagram obtained from first-principles calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 46 publications
(77 reference statements)
3
74
1
Order By: Relevance
“…Even though a number of reconstructions have been observed on the SrTiO 3 (001) surface [24][25][26], we focused on the so-called double-layer-TiO 2 (2×1) surfaces [27,28] because other more complex surfaces are not compatible with the (2×1) reconstruction under study here. It has been found that, on the double-layer-TiO 2 (2×1) surface, the role of O vacancy is the same as that in the missingrow structure described above.…”
Section: (A)mentioning
confidence: 99%
“…Even though a number of reconstructions have been observed on the SrTiO 3 (001) surface [24][25][26], we focused on the so-called double-layer-TiO 2 (2×1) surfaces [27,28] because other more complex surfaces are not compatible with the (2×1) reconstruction under study here. It has been found that, on the double-layer-TiO 2 (2×1) surface, the role of O vacancy is the same as that in the missingrow structure described above.…”
Section: (A)mentioning
confidence: 99%
“…Identified as the only equilibrium surface structures 13,14,15 , the regular TiO 2 -and SrOterminations illustrated in Fig. 1 form a natural basis for our fundamental study addressing the energetics and electronic structure of O adatoms at cubic SrTiO 3 (001).…”
Section: Theorymentioning
confidence: 99%
“…This shows the extensive hybridization between the 3d-e g orbitals of the NN Ti and the two electrons localized at the vacant anionic site. 49,50 A singly and doubly charged oxygen vacancy is formed by removing one and two electrons, respectively, along with an oxygen atom from the defect free system. The local lattice near the vacancy in case of charged computation cells show greater distortions than a neutral cell.…”
Section: A Oxygen Vacancymentioning
confidence: 99%